Whistle blowing intention in relation to perceived organization support, attitude and channels of communication / Nur Zafifa Kamarunzaman …[et al.] - Kamarunzaman, Nur Zafifa; Zawawi, Azlyn Ahmad; Hussin, Zaliha; Campbell, James (Research Management Institute, 2013)
The aims of this study are two folds, to identify whether intention to whistle blow exists; and to ascertain the relationship between perceived organizational support, channels of communication, attitudes and intention to blow the whistle. The study is perceived to be vital to foresee whether the public are aware on the whistle blowing especially on the preferred mechanism to whistle blow. The study was conducted in seven public offices in West Malaysia, involving 516 employees. The findings indicate that all the predicted elements are moderately associated with the act of whistle blowing. On the other hand, channels of communication are proven to be the most dominant variable in whistle blowing. Moreover, internal programs held by the organizations also supported the findings, as they are a powerful tool to create awareness of the importance of blowing the whistle within the organization setting. Meanwhile fair and just treatments by the organization have generated trust and confidence amongst the employees where they feel empowered and a sense of belongingness. Whistle blowing is also perceived as a new commitment by the respondents as reflecting their loyalties to the organization.